Legal Analysis For Mangrove Illegal Logging In Sangkub Area - Fahrul Risyad Ranselengo (Estudiante Law Journal, 2020)
The purpose of this study is to find out the legal analysis of mangrove illegal logging in the Sangkub coastal area. The research method used is the dualism of normative-empirical legal research whereby research uses normative-empirical legal case studies in the form of legal behavioral products.  The approach used is a juridical approach and analytical technique using qualitative analytical methods. The results show that Law Enforcement in the Field of Illegal Logging for environmental sustainability has not been resolved properly. Then many rules must be implemented, but law enforcement looks away with excitement that will damage the environment in coastal areas. Furthermore, forest crimes cannot be solved using forestry instruments alone. What is needed is cooperation between parties such as non-governmental organizations, the Corruption Eradication Commission (KPK), the Police of the Republic of Indonesia (POLRI), and others. To restore the function of mangrove forests as protectors of coastal areas, it is necessary to plan a comprehensive mangrove sustainable rehabilitation program that involves all important elements of conservation areas, namely communities, regional managers, and local governments.Keywords: Logging; Wild; Mangrove.